The Syrian Conflict: A reading on the Regional Dimensions and Implications - LAARID, Hocine; HAMDOUCHE, Riad (Journal of Human Sciences, 2020)
The aim of this study is to shed a light on the impact of the Syrian conflict, as a complex case than in the Arab world, and as an important strategic event in the context of the Arab spring on the regional States in the Middle East, due to the importance of the Syrian geopolitical position Furthermore, its impact on shaping the future of the region, and on shaping the relations between their countries and their peoples. Despite the global nature of the Syrian effects, the Middle East’s Countries are the most affected by geopolitical developments and overlapping of relations and interests in the region, which makes these countries, follow the events in terms of impact on its internal situation and relations with neighboring countries.